Pelatihan Bahasa Inggris Pariwisata Bagi Siswa SMAN 7 Di Pulau Balang Lompo Kabupaten Pangkep: Pelatihan Bahasa Inggris Pariwisata Bagi Siswa SMAN 7 Di Pulau Balang Lompo Kabupaten Pangkep - Sri Ningsih Ningsih; Dirk Sandarupa Dirk Sandarupa; Rusmin Rusmin; Antonius Ali Wutun Antonius Ali Wutun; Ramlan M Ramlan M; Nur Indah Nur Indah; Eka Sapira Rusman Eka Sapira Rusman (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2023)
Balang Lompo Island is located in Pangkep district has the beauty and abundant marine biodiversity that can attract both domestic and global tourists. This community service (PKM) activity was carried out on 7th Pangkep State High School students aimed at improving English-speaking skills in the field of tourism in response to the needs that can promote tourism development in Pangkep district. The methods used in this activity are in the form of memoirs that include interactive learning on the use of English in the context of tourism. The material presented includes vocabulary in the field of Tourism and writing about the potential tourism in the island of Balang Lompoa. The results of PKM showed a significant improvement in the understanding and application of English tourism among students. They responded positively to interactive and contextual learning methods, which helped them internalize English language skills more effectively. This community commitment is expected to make a positive contribution in preparing the younger generation to face the global challenges in the tourism sector. In addition, strengthening English skills is also expected to open up broader opportunities for students in developing careers and contributing to the development of local communities.